Portraits of Mahatma Jyotirao Phule, Chhatrapati Shivaji Maharaj and Dr B.R. Ambedkar - Ghosh, Ayan (2023)
Though externally the BMC building has largely retained Frederick Steven's original design, the interiors have periodically been modified to cater to political and nationalistic compulsions after the end of British rule. Here, for example, portraits of Mahatma Jyotirao Phule, Chhatrapati Shivaji Maharaj, and Dr. B.R. Ambedkar have been added over doorways.